PENGEMBANGAN SISTEM INFORMASI BERBASIS WEBSITE UNTUK PENINGKATAN POTENSI DESA JEMIRAHAN - Astuti, Cindy Cahyaning; Mulyanto, Angga Dwi; Wiguna, Akbar; Hasanah, Fitria Nur; Untari, Rahmania Sri; Nugroho, Oktavianto Ashror (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Village website development is the process of designing, creating and maintaining a website specifically to represent and serve the needs of a village. Websites generally aim to provide an information and communication platform that can be accessed by members of the village community as well as other people interested in the village. . On the Jemirahan Village website, there are several menus, including village structure notifications, news information linked to Facebook, and a suggestion and complaint box menu. In the complaints menu, Jemirahan village residents can provide suggestions or criticism regarding the services provided by Jemirahan village officials. Creating a website for village communities brings various significant benefits, both in social, economic and educational aspects. The website is not only a communication tool, but also a strategic platform for development and empowerment of village communities in various fields.